Perkin-Elmer elemental analyzer in use at Marine Ecology Laboratory - Perkin-Elmer Corporation (1970)
General view of technician Georgina Phillips operating a Perkin-Elmer elemental analyzer in the Marine Ecology Laboratory at the Bedford Institute of Oceanography located in Dartmouth, Nova Scotia, Canada. Per notations accompanying the photograph, Phillips is testing the carbon and nitrogen content of a sediment sample from the Bay of Fundy as part of a determination of the bay's ecosystem constituents.
Keywords: Women in science; Employees; Perkin-Elmer Corporation; Laboratories; Bedford Institute of Oceanography; Corporations; Marine sediments; Women employees; Marine ecology; Scientific apparatus and instruments